Efek pegagan (Centella asiatica L)terhadap proliferasi mesenchymal stem cell (Effect of pegagan (Centella asiatica L)to mesenchymal stem cell proliferation) - Ira Arundina; Ketut Suardita (DiscoverSys Inc., 2014)
Stem cells provide new hope to fasten the healing process of various oral diseases including periodontal tissue(periodontitis). At present time, there is not yet found a material that can fix the teeth perfectly. Adult stem cells frombone marrow widely used for treatment. Numbers of stem cell are limited so growth factor is necessary to promoteproliferation of stem cells. Growth factor that has been used is expensive and difficult to get. Because of theseconstraints, it is necessary to develop alternative uses of medicinal plants as growth factor that accelerates woundhealing process. This study is aimed to proven what extent the potential Pegagan (Centella asiatica L) as a naturalgrowth factors to stem cells. The ability of proliferation and osteogenic differentiation in mesenchymal stem cells(MSC)was analyzed by adding terpenoid fraction of Centella asiatica. MTT assay data showed that the addition ofPegagan on cultured MSCs can increase stem cell proliferation. Pegagan increases the ability of MSC proliferationand differentiate into osteoblasts It is concluded that pegagan increase the ability of MSC proliferation anddifferentiate into osteoblasts.